نظام الكوتا بين التنظيروالتطبيق: تجربة الجزائر نموذجا ( 2012- 2017) - بوحفص, روميلة (University of Eloued جامعة الوادي, 2021)
يعتبر نظام الكوتا الية ناجعة للتمكين السياسي اخذت به الكثير من الدول لتعزيز المشاركة السياسية للمراة في المجالس المنتخبة ، ويندرج هذا النظام ضمن خطة شاملة تصبو لتعميم تطبيق النوع الاجتماعي ،و تستند فكرة هذا النظام الى مبدا التمييز الاجابي لصالح المراة كما نصت عليه اتفاقية سيداو 1979 ،ورغم ان لهذا النظام الكثير من الماخذ والمكاسب ولكن يبقى الطريق الوحيد في نظر الكثير من السياسين والاكادميين الذي يضمن تواجد المراة في مراكز صنع القرار بعدما همشت لسنوات ،و لقد تبنت الجزائر هذا النظام في الانتخابات التشريعية والمحلية التي اجريت سنة 2012 بعد سلسلة قوانين توجت بالمصادقة على القانون العضوي12-03 سنة 2012 المحدد لكيفية توسيع حظوظ المراة بالتواجد في المجالس المنتخبة،والذي سمح بذالك بوصول الكثير من النساء اليها عن طريق قوائم اغلبها حزبية ضمت ما نسبة 30 بالمئة من المقاعد للنساء اجبارا. The quota system is an effective mechanism for political empowerment that many countries have adopted to enhance the political participation of women in the elected councils. This system is part of a comprehensive plan that seeks to generalize the application of gender, and the idea of this system is based on the principle of positive discrimination in favor of women as stipulated in the 1979 CEDAW agreement. Although this system has many drawbacks and gains, it remains the only way in the eyes of many politicians and academics that guarantees the presence of women in decision-making positions after being marginalized for years, and Algeria has adopted this system in the legislative and local elections that were held in 2012 after a series of laws that culminated in the ratification of The organic law 12-03 of 2012 specifying how to expand women's chances of being in elected councils, which allowed that many women to access them through lists of mostly partisan that included 30 percent of the seats forcibly women.
مجلد12، عدد1
Keywords: نظام (الكوتا)- التمكين السياسي- الانتخابات – اتفاقية سيداو – النوع الاجتماعي; quota system; Political empowerment; the election; CEDAW agreement; Gender